Pemanfaatan Limbah Perkebunan Kelapa Sawit Sebagai Sumber Energi Terbarukan - Rina Novia Yanti (Universitas Riau, 2023)
Indonesia is the world's largest palm oil producer with a land area of 14.3 million as of 2019. With this area, it will produce biomass in the form of replanted stems, midribs, empty palm oil bunches (TKKS), shells and fruit fibers. Biomass waste, including palm oil solid waste, has the potential to be used as raw material for renewable energy or bioenergy. This study aims to utilize palm oil plantation waste into bio oil and bio briquettes. The raw materials used in this study were empty oil palm fruit bunches (TKKS) and palm oil shell waste. Bio oil is made by the pyrolysis process. This research produces pyrolysis products, namely bio oil as a substitute for diesel fuel from EFB waste and from shells to produce bio briquettes. Found in pyrolysis products, namely bio-oil, aromatic compounds, aliphatic hydrocarbon compounds, acid compounds and hydrocarbon compounds. Hydrocarbon compounds are compounds that exist in fuel oil. In OPEFB bio oil, 19 types of hydrocarbon compounds were found. Meanwhile, bio briquettes from oil palm shells produce a calorific value of > 5000 which has met the Indonesian national standard (SNI) 01-6235 in 2000. Meanwhile, the water content value meets the Indonesian National Standard, which is a maximum of 15%.